A branch‐and‐bound algorithm for the time‐dependent travelling salesman problem. Issue 3 (19th June 2018) - Arigliano, Anna; Calogiuri, Tobia; Ghiani, Gianpaolo; Guerriero, Emanuela
Abstract : Given a graph whose arc traversal times vary over time, the Time‐Dependent Travelling Salesman Problem consists of finding a Hamiltonian tour of least total duration. In this paper we exploit some properties of the problem and develop a branch‐and‐bound algorithm which outperforms the state‐of‐the‐art branch‐and‐cut procedure by Cordeau et al. [5].